Study on "the intelligent real-time monitor & control system for physical training" - Sun, X.; Chen, H.; Guo, J. (1999)
This study aimed to study the application of the high-tech into sports fields to improve the scientific degree and efficiency of the sports training, to realize "Intelligent biological micro-regulation" in elite athlete's physical training, and to exploit a new area of "the digitalization in sports training" . The techniques of the bio-electronic remote measurement, digitalization, fuzzy controlling, and the Deviation Global Position System (DGPS) were employed to make up "The Intelligent Real-time Monitor & Control System for Physical Training (IRMCS)". The system consists of the 3 sub-systems, GPS dynamic real-time monitor & control system, the medical real-time monitoring & control system and computer central modulation system (CCMS) and it can real-timely monitor & control the changes of physiological and dynamical indexes in elite athletes during the period of the physical training and can make sure that the whole physical training procedures are conformed with the coach's fixed training plan. The system can real-time checks the data changes of physiological & dynamical indexes, such as workload intensity and velocity, in the period of the physical training, and compares the data with that of ones in the fixed training plan by the central modulation system (CMS), and then send out the frequency-modulation orders to the coach and athlete for having the athlete adjust his exercise intensity or movement speed to make the physical training achieves its optimal training effects. The author concludes that the Intelligent Real-time Monitor & Control System for Physical Training (IRMCS) provides a high-tech training mean for the scientific physical training of the elite athletes, especially in the endurance event.